The instrumentalisation of politics and politicians-as-commodities - Amon Prodnik, Jernej (Annales. Series historia et sociologia, 2016)
The article examines current processes in institutional politics and the often discussed tendency towards the professionalisation of political communication. It relates this tendency to the instrumentalisation of political life and its adoption of the commodity logic in public communication. The study proceeds from the perspective of critical theory and the political economy of communication. It connects this theoretical basis to Slovenian institutional politics with the aim to analyse whether and in which ways instrumental reason and commodity logic have been adopted in the political communication of political parties. The study is based on semi-structured, in-depth interviews conducted with key representatives of seven parliamentary and three extra-parliamentary Slovenian parties or groups.
Keywords: Kvalitativna analiza; poblagovljenje; Political communication; Political parties; political party; Politične stranke; Politično komuniciranje; politično znamčenje; Profesionalizacija; Professionalization; Qualitative analysis; Slovenia; Slovenija